Multi-physical field parameter response in the whole process of coal and gas outburst under deep high stress - Qiang ZHANG; Jun NIAN; Bo ZHAO; Wei ZHANG (Meikuang Anquan)
Based on the thermo-fluid-solid coupling law of coal and gas outburst in deep mining, a numerical model of coal and gas outburst is established, and the response of multi-physical parameters in the whole process of coal and gas outburst under high stress condition is analyzed. The results show that the response rule of the stress field around the outburst hole is initial vibration-sudden attenuation-late stability. The decreasing rate of gas pressure is negatively correlated with the length of the outburst hole. In the outburst process, the adsorbed gas contained in the crushed coal quickly desorbed and expanded to do work, resulting in a decrease in temperature; the areas with significant changes in permeability after outburst can be divided into sudden increase area, medium increase area and increase area. With the increase of stress, the proportion of elastic potential in total coal and gas outburst energy increases, and the proportion of elastic potential is positively correlated with stress.